The comparison of Imagery ability in elite, sub-elite and non-elite swimmers - Duarte-Mendes, Pedro (2019)
The ability to generate and control mental images is present in all of us, but it differs from person to person. Therefore, it is important to understand that imagery ability can be changed through training and experimentation, it is not a fixed ability. The aim of this study is to compare imagery ability in elite, sub-elite and non-elite athletes in a sport which involves closed and continuous motor skills, such as swimming. 79 swimmers (male N = 37; female N = 42) at an average age of 17 took part in thisstudy. In order to assess imagery ability, the Movement Imagery Questionnaire 3 was used, Portuguese version (Mendes et al., 2016). After analysis of the results, these show that in each and every imagery modality, the scores in the three groups differ significantly. In kinesthetic and external visual imagery the elite and sub-elite groups’ scores, although not statistically different from each other, are significantly higher than those of the non-elite group. In internal visual imagery, the differences between all the compared pairs of groups are statistically significant. The elite group got the highest scores, followed by the sub-elite group average scores and finally the non-elite group average scores. According to these results, the conclusion is that athletes with a better performance show greater imagery ability and that apparently the external visual imagery proved to be the best intervention method among swimming athletes.